EFFECTIVENESS OF ONLINE-BASED SCHOOL-AGE LEARNING MODEL: GAME QUIDENT MY TEETH IS HEALTHY - Marlindayanti Marlindayanti; Nanda Maharani; Afifatus Syahadah; Dhea Angelia Putri; Fastabiqul Hanif (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2022)
Dental caries in children are still often ignored by parents due to lack of knowledge about the importance of maintaining healthy teeth and mouth. In obtaining knowledge, people can use various media, the media that is widely used by society today is gadgets. Apart from being used as a medium of information, gadgets can also be used as a medium of entertainment and learning. Purpose: to create a Quident game application that can be used to increase children's dental health knowledge in the 9-11 year old group. Method: Design and Creation with the following steps Awareness, Suggestion, Development, Evaluation, and Conclusion. The research sample used random sampling. A total of 10 people tested the Quident game application. Research Results: The Quident game application has been created which is equipped with an animated video with a mascot that was created to educate and motivate users and can evaluate the increase in user knowledge with questionnaires on games, 10 sample people who use the application have no difficulty playing and can complete the game to the last level. Conclusion: Quident games can be used to motivate and increase children's dental health knowledge with Android-based games Suggestion: For future development, games are made more varied and published on the Google Play Store.